Topographical distribution and morphology of NADPH-diaphorase-stained neurons in the human claustrum - Hinova-Palova, Dimka V.; Edelstein, Lawrence; Landzhov, Boycho; Minkov, Minko; Malinova, Lina; Hristov, Stanislav; Denaro, Frank J.; Alexandrov, Alexandar; Kiriakova, Teodora; Brainova, Ilina; Paloff, Adrian; Ovtscharoff, Wladimir (Frontiers in Systems Neuroscience, 2014)
We studied the topographical distribution and morphological characteristics of NADPH-diaphorase-positive neurons and fibers in the human claustrum. These neurons were seen to be heterogeneously distributed throughout. Taking into account the size and shape of stained perikarya as well as dendritic and axonal characteristics, NADPHd-positive neurons were categorized by diameter into three types: large, medium and small. Large neurons ranged from to 25-35µm in diameter and typically displayed elliptical or multipolar cell bodies. Medium neurons ranged from 20-25µm in diameter and displayed multipolar, bipolar and irregular cell bodies. Small neurons ranged from 14-20 µm in diameter and most often displayed oval or elliptical cell bodies. Based on dendritic characteristics, these neurons were divided into spiny and aspiny subtypes. Our findings reveal two populations of NADPHd-positive neurons in the human claustrum - one comprised of large and medium cells consistent with a projection neuron phenotype, the other represented by small cells resembling the interneuron phenotype as defined by previous Golgi impregnation studies.